1994
DOI: 10.1177/001440299406000603
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Policy Study of the Least Restrictive Environment Provision of the Individuals with Disabilities Education Act

Abstract: A multistate, qualitative policy study, conducted from 1989 to 1992, investigated how 6 states and 12 local school districts implemented the least restrictive environment (LRE) provision of the Individuals with Disabilities Education Act (IDEA). Eight sites were relatively high users of separate facilities for educating students with disabilities, and 10 were low users. Six factors, including financing and the state-local context, influenced the implementation of LRE. Although the LRE policy has influenced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…The support and leadership of principals are documented as integral components for successful school change (Fullan 2001) and successful inclusion (Hasazi et al 1994;Simpson 2004). As school-site administrators and policy leaders, principals influence reform implementation decisions, control resource allocations and exert a supervisory role relative to school personnel.…”
Section: Role Of Principalmentioning
confidence: 99%
“…The support and leadership of principals are documented as integral components for successful school change (Fullan 2001) and successful inclusion (Hasazi et al 1994;Simpson 2004). As school-site administrators and policy leaders, principals influence reform implementation decisions, control resource allocations and exert a supervisory role relative to school personnel.…”
Section: Role Of Principalmentioning
confidence: 99%
“…Despite the growing body of research and policy supporting inclusion of students with disabilities in general education settings (Hasazi, Johnston, Liggett, & Schattman, 1994;Osborne & Dimatta, 1994), ample evidence shows that families, schools, and communities are experiencing significant barriers in accomplishing successful inclusion of students with problem behavior (Horner, Diemer, & Brazeau, 1992;Stanford Research Institute, 1990;White, Lakin, Bruininks, & Li, 1991).…”
Section: Figurementioning
confidence: 99%
“…The data suggest a strong family concern about administrator and teacher competency in providing an appropriate education for their children with problem behavior (Erwin & Soodak, 1995;Hasazi et al, 1994). Parents reported that they needed to have information that they could use to convince their school systems about the efficacy of state-of-theart approaches and to urge them to move ahead with staff development.…”
Section: Pervasive Themesmentioning
confidence: 99%
“…Instead, researchers have focused on other important aspects of inclusion, such as school leadership (Billingsley, Gersten, Gillman, & Morvant, 1995;Guzman, 1997;Hasazi, Johnston, Liggett, & Schattman, 1994;Mantle 2005;Walther-Thomas & DiPaola, 2003;Will, 1986), teacher perceptions and preparation (Hersman & Hodge, 2010;Tankersley, Niesz, Cook & Woods, 2007;Watnick & Sacks, 2006), and small learning communities (Duke & Lamar-Dukes, 2007). These studies provide critical information that can inform practitioners at a school-level; however, examining a district's response to important special education mandates is beyond the scope of these studies.…”
Section: Sfusd)mentioning
confidence: 99%